The Fornax Deep Survey with the VST - IV. A size and magnitude limited catalog of dwarf galaxies in the area of the Fornax cluster (Corrigendum) - Venhola, Aku; Peletier, Reynier; Laurikainen, Eija; Salo, Heikki; Iodice, Enrichetta; Mieske, Steffen; Hilker, Michael; Wittmann, Carolin; Lisker, Thorsten; Paolillo, Maurizio; Cantiello, Michele; Janz, Joachim; et al. (Astronomy and astrophysics, 2020)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics